Intercellular adhesion molecule-1 mediates murine colon adenocarcinoma invasion - Howard, Kenton (J Surg Res, 2013)
BACKGROUND: Intercellular adhesion molecule-1 (ICAM-1) modulates cell–cell adhesion and is a receptor for cognate ligands on leukocytes. Upregulation of ICAM-1 has been demonstrated in malignant transformation of adenomas and is associated with poor prognosis for many malignancies. ICAM-1 is upregulated on the invasive front of pancreatic metastases and melanomas. These data suggest that the upregulated ICAM-1 expression promotes malignant progression. We hypothesize that the downregulation of ICAM-1 will mitigate tumor progression. METHODS: Mouse colon adenocarcinoma cells (MC38) were evaluated for the expression of ICAM-1 using Western immunoblot analysis. Short hairpin RNA (shRNA) transduction was used to downregulate ICAM-1. Tumor invasion determined via a modified Boyden chamber was used as a surrogate of tumor progression examining MC38 cells, MC38 ICAM-1 knockdowns, and MC38 transduced with vehicle control. The cells were cultured in full media for 24 h and serum-starved for 24 h. A total of 5 × 10(4) cells were plated and allowed to migrate for 24 h using full media with 10% fetal bovine serum as a chemoattractant. Inserts were fixed and stained with crystal violet. Blinded investigators counted the cells using a stereomicroscope. Statistical analysis was performed by analysis of variance with Fischer protected least significant difference and a P value of <0.05 was considered statistically significant. RESULTS: ICAM-1 was constitutively expressed on MC38 cells. Transduction with anti–ICAM-1 shRNA vector downregulated ICAM-1 protein expression by 30% according to the Western blot analysis (P < 0.03) and decreased ICAM-1 messenger RNA expression by 70% according to the reverse transcription–polymerase chain reaction. shRNA knockdown cells had a significant reduction in invasion >45% (P < 0.03). There were no significant differences between the invasion rates of MC38 and MC38 vehicle controls. CONCLUSIONS: Downregulation of ICAM-1 mitigates MC38 invasion. These data suggest that targeted downregulation of tumor ICAM-1 is a potential therapeutic target.